APLIKASI CERITA HUMA BETANG SEBAGAI SARANA PEMBELAJARAN MENULIS TEKS NARATIF SISWA SMP - Diplan; Helmi; Rahman, Rahman; Fendi Hariatama H; Febria Helena (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
The ability to write narrative texts is a fundamental competency in Indonesian language learning, but various field findings show that junior high school students still face difficulties in determining ideas, developing plots, and comprehensively understanding narrative structures. In this context, the integration of learning technologies that are sensitive to local culture is an urgent need. This study aims to develop and implement the Cerita Huma Betang Application as a medium for learning narrative writing that combines the power of digital literacy with the local wisdom of Central Kalimantan. The method used is Research and Development (R&D) with 30 eighth-grade students from SMP Negeri 6 Palangka Raya as test subjects. The results of the study show that this application contributes significantly to improving students' writing skills. The Read feature, which presents folk tales such as the Legend of Riam Mangkikit and others, has proven to be effective in helping students understand the patterns of orientation, complication, and resolution. The Selecting feature plays a role in facilitating students in choosing themes, characters, settings, and cultural values, so that the writing process becomes more focused. Data showed that 86.7% of students were able to produce more coherent, logical, and creative narrative texts after using the application. In addition, student response to the application has been very positive; its simple display, intuitive navigation, and digital writing space allow students to work more independently. Thus, the Cerita Huma Betang application is considered effective, practical, and relevant as a medium for learning narrative writing based on local culture, as well as being able to support the strengthening of students' digital literacy in the era of modern learning.